USAGE OF CLASSROOM FOR TRAINING AND TESTING OF THE KNOWLEDGE ON INFORMATICS - Yersultanova, Z.S.; Sabit, Z.S. (PUBLISHINGS of Kostanay State Pedagogical University, 2019)
This article discusses how to improve the quality of teaching by organizing virtual learning at the school. It also describes the benefits of virtual learning systems and virtual learning technologies. The conclusions of using Classroom in the educational process are presented.
Keywords: virtual learning; Google Classroom; кnowledge testing; educational process; digital class